Pemikiran Ibnu Khaldun tentang Realitas Sosial dan Relevansinya bagi Pendidikan Islam Modern - Kurnia Alex; St. Nurhayati Ali; Fitriani Muh Amin; ⁠Misbah ⁠Misbah; ⁠Juhariati ⁠Juhariati (FKIP UNSULTRA, 2025)
Ibn Khaldun's thought is one of the important foundations in classical Islamic social and educational studies that remains relevant to the modern context. Ibn Khaldun, through his work Muqaddimah, introduced the concept of social reality as dynamic, historical, and influenced by human interactions in society. This study aims to analyze Ibn Khaldun's thoughts on social reality and examine their relevance in the development of modern Islamic education. This study uses a qualitative approach with a literature study method, namely examining Ibn Khaldun's main works and contemporary literature discussing his thoughts in the social and educational fields. The results show that the concept of 'ashabiyyah, education based on social experience, and the close relationship between science and societal reality are Ibn Khaldun's main ideas that are highly contextual to the challenges of modern Islamic education. Islamic education today is not only oriented towards the transfer of normative knowledge, but must be able to shape social awareness, collective character, and students' adaptive abilities to social change. The relevance of Ibn Khaldun's thought is seen in the importance of integrating Islamic values, social reality, and a contextual and transformative educational approach. Thus, Ibn Khaldun's thoughts can serve as a philosophical foundation for formulating modern Islamic education that is responsive to social dynamics without losing its Islamic identity.